PENDAMPINGAN ONLINE PELATIHAN KETRAMPILAN MEMBUAT TOTE-BAG PADA EX-ANAK ASUH YAYASAN PANTI ASUHAN KRISTEN JAWA TIMUR DI MALANG - Asminah Rachmi; Dwi Sudjanarti; Lilies Nur Ainie; Tatiana Kristianingsih; Tri Istining Wardani (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2021)
The purpose of this community service activity is to assist online training in making tote-bag skills for foster children of the orphanage foundation. The activities are divided into four stages, the first is by preparing a module in the form of a flip-chart containing the required materials and steps to make a tote-bag. The second stage is to form a group-discussion between the target audience through whatsapp-group media and private messages. The third stage is to send the basic materials needed to make products, the last is online assistance. Online assistance includes several steps, namely: Knowledge transfer process, which is an explanation how to make a product based on the flip-chart module, followed by an interactive discussion between members and facilitators using picture-sharing or voice-messages. The final stage is an evaluation of the level of members’ achievements, where each member is required to upload photos of the final knitted product. Based on the final evaluation, it can be concluded that the online mentoring went smoothly and enriched the knowledge and skills of the target audience. Communication was running effectively, as discussions were not limited by space and time, especially during the Covid-19 pandemic the target audiences can continue to learn independently while still being able to maintain their physical-distancing.